Implementation Of Financial Accounting Standards For Entities Without Public Accountability (SAK ETAP) In The Presentation Of Financial Statements Of PT. Siba Concrete Indonesia In Mojokerto - Angga Martha Mahendra; Soesanto Soesanto; Azizah Fitriani; Ayu Nur Mahmudah (International Journal of Economics and Management Research, 2024)
Financial reports contain information concerning the financial position and aims to assist entities in decision making. This research aims to determine whether the financial statements of PT. Siba Beton Indonesia is in accordance with The Indonesian Accounting Standards for Non-Publicly-Accountable Entities (SAK ETAP). This type of research is qualitative. Data obtained by conducting interviews, observation, and documentation. The data analysis technique used by the author is descriptive-comparative analysis by: 1) Presenting the financial statements of PT. Siba Beton Indonesia 2021, 2) Observing, comparing and analyzing the financial reports of PT. Siba Beton Indonesia with SAK ETAP, 3) Draw conclusions about the application of SAK ETAP in the presentation of PT. Siba Concrete Indonesia. The results of data analysis and discussion show that PT. Siba Beton Indonesia has not implemented SAK ETAP and the obstacles in implementing SAK ETAP are significant. This can be proven, namely: 1) The entity has not presented financial statements in a complete and in accordance with SAK ETAP namely balance sheet, income statement, statement of changes in equity, cash flow statement, and notes to financial statements, 2) There are significant obstacles, 3) Efforts to overcome obstacles by providing regular training for employees.